2016
DOI: 10.1039/c5gc01931a
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of indoles via photoredox catalysis: a route to 3-acylindoles

Abstract: A visible-light-catalyzed synthesis of 3-acylindoles from simple indoles and α-oxo acids at room temperature has been discovered. This method offers rapid access to 3-acylindoles through C–C and C–H bond activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 60 publications
0
42
0
1
Order By: Relevance
“…By combining this activation mode with Ni catalysis, aryl ketones could be generated in high yields. 118 It is worth noting that, following this publication, Fu and Shang demonstrated that aryl ketones could also be generated through the merger of photoredox catalysis with Pd catalysis and this transformation likely proceeds via a similar mechanistic pathway. 119 In addition, Wang and co-workers revealed that aryl ketones can be generated by combining photoredox-mediated acyl radical generation with directed Pd-catalyzed C–H activation.…”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 93%
See 1 more Smart Citation
“…By combining this activation mode with Ni catalysis, aryl ketones could be generated in high yields. 118 It is worth noting that, following this publication, Fu and Shang demonstrated that aryl ketones could also be generated through the merger of photoredox catalysis with Pd catalysis and this transformation likely proceeds via a similar mechanistic pathway. 119 In addition, Wang and co-workers revealed that aryl ketones can be generated by combining photoredox-mediated acyl radical generation with directed Pd-catalyzed C–H activation.…”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 93%
“…163 Here, a range of analogues could be readily synthesized by simply employing different tertiary amine coupling partners. In addition, recent advances from our group in the field of metallaphotoredox has enabled the rapid construction of medicinally relevant compounds such as fenofibrate 118 and edivoxetine·HCl 121 (Scheme 34b).…”
Section: Applications Of Photoredox Catalysismentioning
confidence: 99%
“…Non-substituted indole and indoles bearing electron-donating groups such as 5-methylindole and 5-methoxyindole gave the desired products in (Table 4, entries 1-10). Indoles bearing electronpoor group such as 5-uoroindole, 5-chloroindole, 5-bromoindole were also reactive under high temperature and/or extended reaction times (Table 4, entries [11][12][13][14][15][16][17][18][19]. The reaction was highly governed by steric effect as the reaction of 4-bromoindole with propionic and pivalic anhydride afforded the corresponding products in low yields and poor regioselectivity to C3-acylation (…”
Section: Effect Of Substrate Scope For the C3-acylation Of Indole Dermentioning
confidence: 99%
“…[7][8][9][10] However, their synthesis remains challenging and includes N-protection, 11 low yields, 12,13 poor regioselectivity, excess reactants, 14 high temperature, and long reaction time. 11,15,16 Traditional methods involved the use of stoichiometric amounts of Lewis or Brønsted acids for the Friedel-Cras acylation of indole. 11,17,18 Recently, the preparation of 3acylindoles has received much attention and metal-based catalytic pathways have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…MacMillan 课题组在双催化体系下又相继报道了原 位形成的混合酸酐 [25] 、芳基酮羧酸 [26] 、烷基醇 [27] 与芳基 卤代烃的脱羧偶联反应; 期间, Gu 等 [28] 报道了 α-羰基羧 酸与吲哚的脱羧偶联反应; Oderinde 等 [29] 详细阐述了镍 与可见光双催化体系中分子氧、溶剂及光源对交叉偶联 反应的影响; Tong 小组 [30] 则报道了在镍、锌及可见光催 化剂三重作用下的 α-羟基酸-O-羧内酸酐脱除 CO 2 的可 控开环聚合反应.…”
Section: Set 交叉偶联反应unclassified